2023
DOI: 10.1136/bmjopen-2022-063364
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac involvement assessment in systemic sclerosis using speckle tracking echocardiography: a systematic review and meta-analysis

Abstract: ObjectivesCardiac involvement in patients with systemic sclerosis (SSc) is associated with poor prognosis. Early detection of myocardial impairment is essential for treatment. The present study aimed to systematically review the value of detecting subclinical myocardial impairment in SSc patients using myocardial strain obtained from speckle tracking echocardiography (STE).DesignA systematic review and meta-analysis.Data sourcesThe PubMed, Embase and Cochrane library databases were searched in the period from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Longitudinal strain was also used for RV analysis and identified the presence of reduced LV longitudinal strains, despite preserved RV strain in SSc patients without overt cardiac disease [45]. However, a recent meta-analysis revealed that SSc patients have a lower strain than healthy controls for the majority of STE parameters, supporting the presence of impaired myocardium involving both ventricles and atriums [46 ]. Tigen et al [47] reported that left atrial (LA) reservoir and conduit function was similar between the groups, but other studies have reported one or more decreased LA mechanics indices [48][49][50][51].…”
Section: Echocardiography: the Traditional Diagnostic Frontlinementioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal strain was also used for RV analysis and identified the presence of reduced LV longitudinal strains, despite preserved RV strain in SSc patients without overt cardiac disease [45]. However, a recent meta-analysis revealed that SSc patients have a lower strain than healthy controls for the majority of STE parameters, supporting the presence of impaired myocardium involving both ventricles and atriums [46 ]. Tigen et al [47] reported that left atrial (LA) reservoir and conduit function was similar between the groups, but other studies have reported one or more decreased LA mechanics indices [48][49][50][51].…”
Section: Echocardiography: the Traditional Diagnostic Frontlinementioning
confidence: 99%
“…Although the STE results are promising for the early detection of SSc cardiac involvement, the meta-analyses of STE studies showed a significant heterogeneity. This can be explained in part by the differences in studied population, equipment and/or software used to detect myocardial strain [46 ▪ ].…”
Section: Introductionmentioning
confidence: 99%